Pico-hydro systems: microgrid-connection approaches - Leite, V. (2018)
Small hydropower systems are considered an environmentally friendly energy option. They have a huge untapped potential which allows them to make a more significant contribution to future energy demand with many advantages. The integration of pico-hydro systems into microgrids is an emerging solution for the electrification of remote areas and for self-sustainable power systems. This paper presents and discusses the three main grid connection approaches for pico-hydro systems focused on the integration in small microgrids: using specifically designed power converters, using standard wind inverters and using standard photovoltaic inverters. These latest approaches based on conventional inverters are able to explore a large amount of feasible sites with low-head and very low-head. They improve efficiencies, reduce costs and environmental impacts and improve reliability. Experimental evaluation of the performance in steady-state and in dynamic conditions proves the feasibility of these innovative approaches.